Language mixing and exoskeletal theory: A case study of word-internal mixing in American Norwegian - Grimstad, Maren Berg; Lohndal, Terje; Åfarli, Tor A. (Nordlyd, 2015)
This paper discusses word-internal mixing in American Norwegian. The data show that the functional vocabulary is Norwegian whereas many of the lexical content items come from English. We argue that language mixing provides important evidence for grammatical theory: Specifically, the data support a late-insertion exoskeletal model of grammar like Distributed Morphology, in which the primitives of syntax are abstract feature bundles (morphemes) and bare roots. In such a theory, the structure is a separate entity, a sort of skeleton or frame, built of abstract morphemes. The phonological exponents of the roots and abstract morphemes are inserted late into designated slots. We show how such a model can explain the observed pattern for mixing within verb phrases and noun phrases in American Norwegian.